High‐resolution structures of the d‐alanyl carrier protein (Dcp) DltC from Bacillus subtilis reveal equivalent conformations of apo‐ and holo‐forms. Issue 18 (17th July 2015) - Zimmermann, Stephan; Pfennig, Sabrina; Neumann, Piotr; Yonus, Huma; Weininger, Ulrich; Kovermann, Michael; Balbach, Jochen; Stubbs, Milton T.
Abstract : d ‐Alanylation of lipoteichoic acids plays an important role in modulating the properties of Gram‐positive bacteria cell walls. Thed ‐alanyl carrier protein DltC from Bacillus subtilis has been solved in apo‐ and two cofactor‐modified holo‐ forms, whereby the entire phosphopantetheine moiety is defined in one. The atomic resolution of the apo‐ structure allows delineation of alternative conformations within the hydrophobic core of the 78 residue four helix bundle. In contrast to previous reports for a peptidyl carrier protein from a non‐ribosomal peptide synthetase, no obvious structural differences between apo‐ and holo‐ DltC forms are observed. Solution NMR spectroscopy confirms these findings and demonstrates in addition that the two forms exhibit similar backbone dynamics on the ps–ns and ms timescales. Abstract : Crystal structures of DltC in apo‐ and cofactor‐modified forms are presented. The entire phosphopantetheine moiety is defined in one holo‐ DltC crystal form. No major structural differences are observed between apo‐ and holo‐ DltC forms. NMR spectroscopic studies demonstrate similar backbone dynamics of both forms. Carrier protein plasticity in natural product biosynthesis should be reconsidered.